Evolution of Plastic Anisotropy for the Polycrystalline Materials in Large Deformation Processes - Kowalczyk, K. (Engineering Transactions, 2001)
Model of evolution of plastic anisotropy due to crystallographic texture development in metals subjected to large deformation processes is presented. The rigid-plastic model of single grain with regularized Schmid law proposed by Gambin is used. Phenomenological and physical descriptions of plastic flow of polycrystals are discussed. Properties of any yield function for orthotropic material subjected to the plane stress state are outlined. Yield conditions of degree m proposed by Hill and Barlat with Lian are analyzed. Finally, phenomenological texture-dependent yield surface is proposed. Evolution of this yield surface is compared with phenomenological yield conditions for two processes: rolling and pure shear.